Development of Ti-15Zr-Mo alloys for applying as implantable biomedical devices - Correa, D. R.N.; Kuroda, P. A.B. [UNESP]; Lourenço, M. L. [UNESP]; Fernandes, C. J.C. [UNESP]; Buzalaf, M. A.R.; Zambuzzi, W. F. [UNESP]; Grandini, C. R. [UNESP] (Elsevier, 2018)
In this study, the effect of molybdenum content in Ti-15Zr-based alloys (wt%) was analyzed in terms of crystalline structure, microstructure, selected mechanical properties, and cytotoxicity. The samples were produced by argon arc-melting followed by hot rolling and heat treatment processes. The crystalline structure and microstructure were dependent of both alloying elements (zirconium and molybdenum). Ti-15Zr alloy displayed only laths of α′ phase, while the alloys up to Ti-15Zr-10Mo exhibited different proportions of α′ α” and β phases. Molybdenum content higher than 12.5 wt% fully stabilized the β phase. Vickers microhardness values of Ti-15Zr-Mo alloys were higher than those of CP-Ti due to solid solution and phase precipitation strengthening. Young's modulus values of Ti-15Zr-Mo alloys were lower than those of CP-Ti due to β phase stabilization. Cytotoxicity levels of Ti-15Zr-Mo alloys were within a tolerable range for biomedical purposes. In addition, we observed molybdenum content in Ti-15Zr-based alloys promoted an increase on pre-osteoblast adhesion up to 3 h of adhesion's time. Thus, Ti-15Zr-15Mo alloy presented better combination of properties than some traditional metallic biomaterials.
Keywords: Biomaterial; Mechanical properties; Microstructure; Titanium alloys